Resolução CSMPF nº 1, de 26 de agosto de 1993 - Aristides Junqueira de Alvarenga; Jose Arnaldo da Fonseca; Moacir Antonio Machado da Silva; Miguel Frauzino; Claudio Lemos Fonteles; Alvaro Augusto Ribeiro Costa; Antonio Fernando Barros e Silva de Souza; Francisco Jose; Delza Curvello Rocha; Favila Ribeiro (DJ, Brasília, DF, 28 ago. 1993. Seção 1, p. 19962., 1993)
Dispõe sobre o Regimento Interno Provisório do Conselho Superior do Ministério Público Federal.